Analisis pemasaran sapi potong melalui analisis marjin, transmisi harga, struktur pemasaran, perilaku pemasaran dan kinerja pemasaran - Eko Nugroho (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
Characteristics of respondents the majority (54.38%) were at a productive age,  in the study area had a low educational background were 89.28% the elementary school. Respondents (49.12%) had more than 20 years of farming experience. Ongole Crossbreed (PO) were the most preferred cattle raised by the majority of respondents (57.89%). The respondents mostly (94.74%) sold their cattle to the local trader or middlemen. Who sold their cattle directly to the animal market opted Pakis as the most preferred location (40.35%). The majority of respondents (68.42%) agreed that middlemen played a crucial role in determining the selling price. The selling price of cattle in producers level has a low correlation (r = 0.32) with price in the traders level. Also, the price transmission was low (0.00099). The farmers earned monthly on average Rp 113.160 per animal, the local traders Rp 375.000 per animal. This low-income share caused by the fact that farmers should pay production costs as an amount of Rp 2.329.772 per animal per year or Rp 194.147 per animal per month.